Multilevel optical data storage in a Eu2+/Ho3+ doped Ba2SiO4 phosphor with linear mapping between ultraviolet excitation and a thermoluminescence/photostimulated luminescence response. Issue 2 (16th December 2021) - Pan, Mingliang; Zhong, Yi; Lin, Hui; Bao, Hongran; Zheng, Lulu; Hong, Ruijin; Dai, Bo; Yu, Dechao; Zhang, Dawei; Zhuang, Songlin
Abstract : Multilevel optical storage is realized by using a Ba2 SiO4 : Eu 2+, Ho 3+ phosphor due to its linear property between excitation and optical/thermal stimulation response. Abstract : Persistent luminescence phosphors are regarded as one of the promising candidates for optical storage media. However, most optical storages using phosphors can only realize single-bit-data recording, limiting the storage capacity. In this paper, we propose a multilevel intensity-multiplexing optical storage scheme, in which Ba2 SiO4 : Eu 2+, Ho 3+ phosphor films are used as the storage media. The scheme is based on the finding that if the thermal or near-infrared stimulation is fixed to a constant, the luminescence response is linearly proportional to the excitation power. Besides, the linearity can be maintained with different delays after the excitation was stopped. Thus, the write-in and read-out signal powers can be quantized into multiple levels for representing multiple bits. Optical storage of grayscale images and multilevel data is demonstrated. The bit error rate in optical data storage is less than 1.6%. The phosphor film is erasable and rewritable for recording multilevel data. The present work paves a way for high-capacity storage using persistent luminescence phosphors.